A dialogue between the humanities and social sciences: cultural landscapes and their transformative potential for social innovation - Panagiotopoulos, Diamantis; Wallenwein, Fabienne; Mildenberger, Georg; Schimpf, Gudrun-Christine (Heritage, 2023)
Throughout the last decades, engaging with cultural landscapes has been a scientific, social, ethical, political, and economic imperative that calls for novel theoretical approaches, effective strategies and, above all, participatory action. Facing this multifarious challenge, academic disciplines have to redefine their traditional methods and aims, and demonstrate an openness towards new and risky paths of scientific pursuits. The present paper arose from interdisciplinary cooperation between the humanities and social sciences with the main objective to explore the potential of cultural landscapes as resources for social innovation in rural regions, addressing issues such as out-migration of original inhabitants, unemployment, and an overaging population. Based on an overview of landscape semantics and theoretical approaches, the paper first analyzes (cultural) landscape and social innovation as applied concepts. In a second step, both disciplinary angles mingle into a joint approach. Moving from methodologies to challenges, the authors discuss the Social Grid Model, which allows for an integrated analysis of social networks, institutions, and cognitive frames. They also delve into the Structured Democratic Dialogue as a tool for the revitalization of ‘active’ and ‘inactive’ cultural landscapes by reinforcing the role of local communities. Finally, the authors investigate how such novel ideas for the promotion of tangible and intangible heritage in rural habitats can be employed by example of two intervention regions in Greece (Koumasa) and the People’s Republic of China (Honghe Hani Rice Terraces), and as part of an orchestrated collective action.
Gesehen am 14.11.2024